Mathematical concepts in mengkuang weaving motifs / Wan Norliza Wan Bakar … [et al.] - Wan Bakar, Wan Norliza; Shamsuddin, Rozita; Muhammad, Rahaidah; Raja Mohd Yusoff, Raja Norazila (2019)
The issues relating to craft preservation has been on the agenda of national, regional, as well as international bodies. Heritage issues have remained in the domain of national governments and regional bodies. While recognizing that heritage issues are incorporated into the national cultural plan-of-action, the priorities set by national governments, more often than not, regard culture a comparatively lower priority. This naturally poses a constraint in terms of the funds allocated to meet the needs of the cultural programs which in turn, affects the efforts to preserve the arts and crafts tradition (Syed Zulfilda S M Noor, 2001). Malaysian Handicraft Development Corporation (MHDC) was given the task to stimulate participation in, encourage and promote traditional skills and handicrafts into becoming a commercially viable concern and to foster its growth from the cottage industry to reach the level of a small-scale industry. There are skills training programs in handloom-weaving, mat making, wood-carving, pottery, rattan and bamboo-weaving, horn ware and batik. MHDC also undertakes product design, development and promotion and provides marketing advisory services (Syed Zulfilda S M Noor, 2001). Weaving is a traditional form of art inherited from our ancestors without any external foreign influences. Weaving involves the process of criss crossing raw materials obtained from special selected plants to be formed into usable products. There are six types of weaving which are mengkuang leaves weaving, pandan leaves weaving, Wild bornean sago leaves weaving, rattan core weaving, coconut leaves weaving and fern leaves weaving. Mengkuang weaving involves the same process of criss crossing the dried processed mengkuang leaves in making mats and other handicrafts as a leisure time activity. Kelarai are designs found in the mengkuang weaving motifs.